САУМА. Дизайн как культурное взаимодействие - -, - (проект байкал, 2006)
«SAUMA. Design as Cultural Interface»–this is the name of the exhibition of Finnish design works that took place in the new building of the Embassy of Finland in Washington. Specialists consider it to be the most intriguing collection of the contemporary Finnish design exhibited in Washington since 2001. The Finnish word «sauma» means junction, boundary, and in the colloquial language–a chance to try something new. The «SAUMA» project is 2 years old. It involves innovational individual works. After its opening in October 2005 in Washington, the exhibition will move to New York and then people of the north American cities will have an opportunity to visit it during two more years.